2022
DOI: 10.1039/d1sc07080k
|View full text |Cite
|
Sign up to set email alerts
|

Principles of melting in hybrid organic–inorganic perovskite and polymorphic ABX3 structures

Abstract: Four novel dicyanamide-containing hybrid organic-inorganic ABX3 structures are reported, and the thermal behaviour of a series of nine perovskite and non-perovskite [AB(N(CN)2)3] (A = (C3H7)4N, (C4H9)4N, (C5H11)4N; B = Co,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Variable‐temperature magnetic susceptibility ( χ m ) measurements for 1 and 1‐G showed similar weak antiferromagnetic interactions between the adjacent Ni II ions (Figure S6), and indicated that the χ m T value of 1‐G is slightly lower than 1 by ca . 0.03 cm 3 mol K −1 at room temperature (Figure 3d), similarly observed in the documentedmetal‐dicyanamide hybrid crystals with lower χ M T values in glassy states, [35] implying a slightly changed coordination configuration in 1‐G . Upon heating, their χ M T curves gradually overlap at above T x , revealing a completely restored coordination configuration after a full recrystallization.…”
Section: Figuresupporting
confidence: 73%
“…Variable‐temperature magnetic susceptibility ( χ m ) measurements for 1 and 1‐G showed similar weak antiferromagnetic interactions between the adjacent Ni II ions (Figure S6), and indicated that the χ m T value of 1‐G is slightly lower than 1 by ca . 0.03 cm 3 mol K −1 at room temperature (Figure 3d), similarly observed in the documentedmetal‐dicyanamide hybrid crystals with lower χ M T values in glassy states, [35] implying a slightly changed coordination configuration in 1‐G . Upon heating, their χ M T curves gradually overlap at above T x , revealing a completely restored coordination configuration after a full recrystallization.…”
Section: Figuresupporting
confidence: 73%
“…The increased propensity toward glass formation after a certain degree of mass loss has also been recently reported in metal− organic frameworks and organic ligand (nonhalide) based perovskites, and is thought to arise from substantial ligand decomposition. 36,37 The mechanism that results in the hindered reorganization of a melt into a crystalline structure after mass loss remains unclear and is a topic of interest for future study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[7,8] Recent years have witnessed emerging studies on solid-liquid transitions in the hybrid crystals consisting of metal-ligand coordination units/polymers being of significance in both theory and application. [9][10][11][12][13][14][15] For instance, hybrid glasses prepared by melt quenching metal-organic frameworks (such as ZIF-4) provided a new platform for extending amorphous materials, [16] whose mechanical properties associated with the inner coordination bonds could be tuned by changing components. [17][18][19][20] By mixing the molten (i-PrNHMe 2 )[fac-Cd(SCN) 3 ] and (MeNHEt 2 )[mer-Cd(SCN) 3 ] in different ratios at relatively low temperature (120 °C), a series of solid solutions were obtained with tuned nonlinear-optical switching temperature in a wide range of 273-328 K. [21] However, the majority of coordination-containing hybrid crystals does not undergo solid-liquid transitions but irreversibly decompose upon heating, and the studies on their solid-liquid transitions are still in the infant stage.…”
Section: Introductionmentioning
confidence: 99%
“…Organic‐inorganic hybrid crystals have shown their promising potentials to develop applicable phase‐transition materials such as ferroic materials, [1–4] dielectric switches, [5,6] and nonlinear‐optical switches [7,8] . Recent years have witnessed emerging studies on solid‐liquid transitions in the hybrid crystals consisting of metal‐ligand coordination units/polymers being of significance in both theory and application [9–15] . For instance, hybrid glasses prepared by melt quenching metal‐organic frameworks (such as ZIF‐4) provided a new platform for extending amorphous materials, [16] whose mechanical properties associated with the inner coordination bonds could be tuned by changing components [17–20] .…”
Section: Introductionmentioning
confidence: 99%